2023
DOI: 10.21203/rs.3.rs-2524306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Study of Corrosion Inhibition of Carbon Steel in Acidic Environment Using Natural Guar Gum

Abstract: Steel is considered as a versatile material due to intrinsic mechanical properties and potential technological applications. However, environmental exposure inevitably oxidize and cause catastrophic industrial failures. To mitigate the oxidation of steel, various prevention methods are adopted, which are toxic and expensive. Herein, an eco-friendly and inexpensive approach is studied to prevent carbon steel from oxidation in the HCl environment. Biodegradable, non-ionic and water-soluble green inhibitor contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Comparative study of the inhibitory effects of various parts of plants (leaves, fruits, barks, nuts, and seeds) have been conducted on mild steel, and stainless steel in acidic, alkaline, and neutral media using Gravimetric methods (weight loss), Potentiodynamic polarization (PDP) and Electrochemical impedance spectroscopy (EIS) techniques [43][44][45] . These studies have reported high inhibition e ciencies with inhibition e ciency increasing with increasing inhibitor concentration 40,[48][49][50][51][52][53] . Prior work indicates that the adsorption of plant extracts on mild and stainless-steel takes place by either physisorption and/or chemosorption depending on the plant extract phytochemicals and the corrosive media 31,42,54,55 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparative study of the inhibitory effects of various parts of plants (leaves, fruits, barks, nuts, and seeds) have been conducted on mild steel, and stainless steel in acidic, alkaline, and neutral media using Gravimetric methods (weight loss), Potentiodynamic polarization (PDP) and Electrochemical impedance spectroscopy (EIS) techniques [43][44][45] . These studies have reported high inhibition e ciencies with inhibition e ciency increasing with increasing inhibitor concentration 40,[48][49][50][51][52][53] . Prior work indicates that the adsorption of plant extracts on mild and stainless-steel takes place by either physisorption and/or chemosorption depending on the plant extract phytochemicals and the corrosive media 31,42,54,55 .…”
Section: Introductionmentioning
confidence: 99%